Pseudolitochira integra (Miers, 1884) (Crustacea: Brachyura: Pilumnidae): redescribed and illustrated from micro-ct scanning the type female - Ng, Peter K.l.; Clark, Paul F.; Clark, Brett; Kamanli, Seyit A. (Zootaxa, 2021)
The taxonomy of the poorly known pilumnid crab, Pseudolitochira integra (Miers, 1884), has been confused because the original description and figures of the type female have inaccuracies, and the specimen has not been examined in detail since the original publication. Consequently, numerous specimens from the Indo-West Pacific have been incorrectly assigned to P. integra, suggesting that this species is widely distributed. The type female was micro-CT scanned in order to provide video and accurate figures of this rare pilumnid. The female possesses a suite of carapace and pereopodal characters that distinctly distinguish it from other pilumnoid taxa. The species is redescribed, refigured and formally designated as the type species of Pseudolitochira Ward, 1942. The identities of the numerous specimens assigned to P. integra are discussed and the distribution of the species is restricted to the western Indian Ocean for the time being.